Heme-Dependent and Independent Soluble Guanylate Cyclase Activators and Vasodilation - Priviero, Fernanda B. M. [UNESP]; Webb, R. Clinton (Lippincott Williams & Wilkins, 2010)
Since the discovery of nitric oxide (NO), which is released from endothelial cells as the main mediator of vasodilation, its target, the soluble guanylyl cyclase (sGC), has become a focus of interest for the treatment of diseases associated with endothelial dysfunction. NO donors were developed to suppress NO deficiency; however, tolerance to organic nitrates was reported. Non-NO-based drugs targeting sGC were developed to overcome the problem of tolerance. In this review, we briefly describe the process of sGC activation by its main physiological activator NO and the advances in the development of drugs capable of activating sGC in a NO-independent manner. sGC stimulators, as some of these drugs are called, require the integrity of the reduced heme moiety of the prosthetic group within the sGC and therefore are called heme-dependent stimulators. Other drugs are able to activate sGC independent of heme moiety and are hence called heme-independent activators. Because pathologic conditions modulate sGC and oxidize the heme moiety, the heme-independent sGC activators could potentially become drugs of choice because of their higher affinity to the oxidized enzyme. However, these drugs are still undergoing clinical trials and are not available for clinical use.
Keywords: soluble guanylyl cyclase activators; nitric oxide; vascular smooth muscle; endothelial dysfunction; vascular disease